2017
DOI: 10.1080/00365521.2017.1328989
|View full text |Cite
|
Sign up to set email alerts
|

Continuing use of antithrombotic medications for patients with bleeding gastroduodenal ulcer requiring endoscopic hemostasis: a case–control study

Abstract: Low prevalence of H. pylori infection, frequent duodenal location, and high rebleeding rate are characteristics of patients with bleeding gastroduodenal ulcer under antithrombotic medications. Continuation of antithrombotic medications can be accepted for bleeding gastroduodenal ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[4][5][6][7] Peptic ulcers are roughly divided into gastric ulcers and duodenal ulcers (DUs) by their anatomic location, and bleeding DUs are frequently reported to be associated with worse outcomes. [9][10][11] Furthermore, DUs can originate from two anatomically subdivided areas: "the bulb" and "the post-bulbar area." 12 Although bleeding from post-bulbar DUs (PBDUs) can become a source of UGIB, the whole picture of the disease is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Peptic ulcers are roughly divided into gastric ulcers and duodenal ulcers (DUs) by their anatomic location, and bleeding DUs are frequently reported to be associated with worse outcomes. [9][10][11] Furthermore, DUs can originate from two anatomically subdivided areas: "the bulb" and "the post-bulbar area." 12 Although bleeding from post-bulbar DUs (PBDUs) can become a source of UGIB, the whole picture of the disease is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more patients in the antithrombotic group suffered more severe illness and required endoscopic hemostasis combining with interventional therapy to stop bleeding and reduce the mortality rate. And study showed that rebleeding rate in the antithrombotic group is significantly higher than that in the control group (13.9% versus 5.8%, P = 0:02) than in the controls [9]. Tracheal intubation and ventilator support can maintain an open respiratory tract and prevent hypoxemia and aspiration caused by gastrointestinal bleeding, particularly in patients with acute upper gastrointestinal bleeding after cardiac surgery or those taking antithrombotic agents.…”
Section: Discussionmentioning
confidence: 90%
“…In terms of prognosis and application of antithrombotic drugs (Table 2), we found that elderly patients had a longer hospital stay, a higher proportion of patients with a history of antiplatelet drugs, and a higher proportion of patients who used anticoagulants during hospitalization. The median time for elderly patients to use antiplatelet drugs after admission was 10 [4, 14] days, and the median time for using anticoagulant drugs was 6 [3,13] days. The median time for young patients to use antiplatelet drugs after admission was 8 [3,13] days, and the median time for using anticoagulant drugs was 8 [4,11] days.…”
Section: Resultsmentioning
confidence: 99%